Audio-lingual scale and teachers’ effectiveness as correlates of oral english performance among high-achieving students in Ibadan, Oyo State (2020)
This study examined the audio-lingual scale and teachers' effectiveness as correlates of Oral English performance among high-achieving students in Ibadan, Oyo State. A descriptive survey design of correlational type was adopted for the study. Purposive sampling technique was used to select four public and private secondary schools in Ibadan North and Akinyele Local Government Areas, Ibadan, Oyo State with a total number of 258 high-achieving students. Instruments used were: English Language Achievement Screening Test (r -0.72), Achievement Test on Oral English (r=0.84), Audio-lingual Method Scale (r= 0.76) and Teachers’ Effectiveness Scale (r-85), Questionnaire (r-0.91). Data were analysed, using Multiple Regression. There was a joint contribution of the two independent variables to high-achieving students’ oral English performance (F(5.52)=55.225, R2= 0.62). Audio- lingual scale (β=185, p<.05) and teachers’ effectiveness (β=197, p<.05) relatively contributed to oral English performance of the respondents. Audio- lingual scale and teachers’ effectiveness correlated with high- achieving students’ oral English performance in Ibadan. Teachers of English are therefore employed to make appropriate use of an audio-lingual method such that it will foster the interest of the learners in attaining masterly level required to use English effectively for verbal communication purposes